Person-centered antenatal care and associated factors in Rwanda: a secondary analysis of program data - Miller, Phoebe (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Research suggests that women’s experience of antenatal care is an important component of high-quality antenatal care. Person-centered antenatal care (PCANC) reflects care that is both respectful of, and responsive to, the preferences, needs, and values of pregnant women. Little is known in Rwanda about either the extent to which PCANC is practiced or the factors that might determine its use. This is the first study to quantitatively examine the extent of and the factors associated with PCANC in Rwanda. METHODS: We used quantitative data from a randomized control trial in Rwanda. A total of 2150 surveys were collected and analyzed from 36 health centers across five districts. We excluded women who were less than 16 years old, were referred to higher levels of antenatal care or had incomplete survey responses. Both bivariate and multivariate logistic regression analyses were used to test the hypothesis that certain participant characteristics would predict high PCANC. RESULTS: PCANC level was found to be sub-optimal with one third of women leaving antenatal care (ANC) with questions or confused and one fourth feeling disrespected. In bivariate analysis, social support, greater parity, being in the traditional care (control group), and being from Burera district significantly predict high PCANC. Additionally, in the multivariate analysis, being in the traditional care group and the district in which women received care were significantly associated with PCANC. CONCLUSIONS: This quantitative analysis indicates sub-optimal levels of PCANC amongst our study population in Rwanda. We find lower levels of PCANC to be regional and defined by the patient characteristics parity and social support. Given the benefits of PCANC, improvements in PCANC through provider training in Rwanda might promote an institutional culture shift towards a more person-centered model of care.